Impact of vitamin D on ultraviolet-induced photoaging and skin diseases - Sankalya S. Ambagaspitiya; Gayan A. Appuhamillage; Rohan S. Dassanayake (Open Exploration Publishing Inc., 2024)
Excessive exposure to ultraviolet (UV) radiation causes premature aging of the skin, known as photoaging. UV radiation induces DNA damage, oxidative stress, inflammatory reactions, and degradation of extracellular matrix (ECM) proteins, contributing to the aged skin phenotype. The skin synthesizes vitamin D upon UVB exposure, which plays a pivotal role in the proper function of multiple body systems. Vitamin D protects skin from photo-damage by repairing cyclobutane pyrimidine dimers, reversing oxidative stress, and reducing chronic inflammation. Moreover, various epidemiological studies have identified vitamin D deficiency as a marker for common dermatological disorders. Improvement of clinical outcomes with vitamin D supplementation further suggests its protective role against skin pathologies. This review comprehensively covers the involvement of vitamin D in combating UV-induced photoaging and various skin disorders, highlighting the significance of maintaining vitamin D adequacy for healthy skin.